Bone fractures in patients with type 2 diabetes mellitus: prevalence and risk factors - Tatiana Olegovna Yalochkina (Endocrinology Research Centre, 2016)
Aim. To estimate the prevalence of and risk factors for low-traumatic fractures in patients with type 2 diabetes mellitus (T2DM).Materials and methods. We questioned 214 patients with T2DM from a single outpatient clinic located in Moscow to evaluate the prevalence of and risk factors for low-traumatic fractures, the duration of and complications from TD2M and HbA1c levels.Results. Of 214 patients, 65 reported low-traumatic bone fractures. Patients with a history of low-traumatic fractures reported falls in the previous year (28%), whereas only 13% of patients without fractures reported falls. The difference was statistically significant, with an odds ratio of 2.34 (1,14–4,76), P=0,022. Men reported fractures more frequently than women (43.3% vs. 24.7%, respectively, P = 0.01). Patients with bone fractures had a lower body mass index (P = 0.022); however, a multivariate analysis revealed that a history of falls and male sex were the most significant risk factors for fracture.Conclusion. Around 30% of patients with T2DM from a Moscow outpatient clinic reported bone fractures. The most significant risk factors for fracture were a history of falls in the previous year and male sex.